The Effect of Thinking Maps in Problem Based Learning Learning Models on Students' Science Literacy Competence - Ety Kurniati (Experimental Student Experiences, 2023)
This study aims to determine the effect of thinking maps in the problem based learning (PBL) learning model on students' scientific literacy competencies. This type of research is a quasi-experimental design with a pretest posttest control group design. The sampling technique for the experimental and control classes used random cluster sampling. The subjects of this study were 68 students of SMAN 1 Kota Bima which were divided into 2 classes, namely 34 students as the experimental class and 34 other students as the control class. Students in the experimental class were taught using the PBL learning model assisted by thinking maps, while students in the control class were taught using the PBL learning model. This study used a competency scientific literacy test instrument in the form of 13 items with a reliability of 0.489. Research data were analyzed by one tail t test. The results of the scientific literacy competency t test of students obtained tcount = 2.89 > 2 = ttable (0.05; 66), indicating that the scientific literacy competence of students who learn by using thinking maps in the PBL learning model is higher than students who study with the PBL learning model.